Smoothing state tax revenues over the business cycle: Gauging fiscal needs and opportunities - Yolanda K. Kodrzycki (Federal Reserve Bank of Boston, 2014)
The high degree of fiscal stress experienced by state governments in the 2001 and the 2007-2009 recessions has prompted renewed discussions of alternative approaches to stabilizing state finances over the business cycle. Prompted by evidence of increased state tax revenue cyclicality in the aggregate, this study explores state-specific patterns so as to inform policymakers in individual states. It finds that while elasticity levels continued to differ across states, most states experienced greater cyclical sensitivity in the 2000s than in the 1980s and 1990s. In addition, during the 2000s personal income tax receipts varied more over the business cycle than sales tax receipts in most states that imposed both forms of taxation. This trend represented a departure from the patterns of the prior two decades, when sales tax receipts were more cyclically sensitive than individual income tax receipts in the majority of states. Cross-section regressions reveal that the main source of variation in income tax elasticities across states during the 2000s was the cyclical sensitivity of their residents' incomes as reflected on their federal income tax returns. By contrast, state-specific features such as the tax treatment of capital gains or the progressivity of tax rates did not account for significant differences in revenue elasticities across states. In addition, state departures from the federal definitions of adjusted gross income and taxable income, on the whole, did not contribute to increased revenue volatility over the business cycle. The findings are used to evaluate the efficacy of alternative measures that could be used to help stabilize state revenues, including reforms of state tax and stabilization trust structures.
Keywords: H2; H7; 330; state tax policy; revenue cyclicality; tax volatility; individual income tax